SALMO and S3M: A Saliva Model and a Single Saliva Salt Model for Equilibrium Studies - Francesco Crea; Concetta De Stefano; Demetrio Milea; Alberto Pettignano; Silvio Sammartano (Bioinorganic Chemistry and Applications)
A model of synthetic saliva (SALMO, SALiva MOdel) is proposed for its use as standard medium in in vitro equilibrium and speciation studies of real saliva. The concentrations come out from the literature analysis of the composition of both real saliva and synthetic saliva. The chief interactions of main inorganic components of saliva, as well as urea and amino acids, are taken into account on the basis of a complex formation model, which also considers the dependence of the stability constants of these species on ionic strength and temperature. These last features allow the modelling of the speciation of saliva in different physiological conditions deriving from processes like dilution, pH, and temperature changes. To simplify equilibrium calculations, a plain approach is also proposed, in order to take into account all the interactions among the major components of saliva, by considering the inorganic components of saliva as a single 1 : 1 salt (MX), whose concentration is cMX=(1/2)∑ci (ci = analytical concentration of all the ions) and z ion charge calculated as z=±(I/cMX)1/2 = ±1.163. The use of the Single Saliva Salt Model (S3M) considerably reduces the complexity of the systems to be investigated. In fact, only four species deriving from internal ionic medium interactions must be considered.